Reviewers’ views on the editorial review processes of the Canadian Medical Education Journal - Larisa Lotoski; Jennifer O’Brien; Marcel F D’Eon (Canadian Medical Education Journal)
Background: Peer review is an integral part of the scientific process, ongoing efforts are needed to improve this process for both the reviewer and the scientific journal conducting peer review. This work describes the Canadian Medical Education Journal (CMEJ) peer reviewers’ experiences in accepting or declining invitations to review.